2003
DOI: 10.1111/j.1523-5378.2003.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Helicobacter pylori Infection Improves Blood Pressure Values in Patients Affected by Hypertension

Abstract: Our study demonstrated a significant decrease in blood pressure values, in particular in diastolic blood pressure values, after H. pylori eradication in hypertensive patients. A high prevalence of CagA positivity was found. The association between cardiovascular disease and H. pylori infection seems pronounced only in CagA-positive patients. The possible links between hypertensive disease and H. pylori infection may involve the activation of the cytokine cascade with the release of vasoactive substances from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 26 publications
2
40
0
5
Order By: Relevance
“…It has been reported that H. pylori eradication improves BP values in patients affected by hypertension. The link between hypertensive disease and H. pylori was related to a possible activation of the cytokine cascade with the release of vasoactive substances from the primary site of H. pylori colonization [11-13]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that H. pylori eradication improves BP values in patients affected by hypertension. The link between hypertensive disease and H. pylori was related to a possible activation of the cytokine cascade with the release of vasoactive substances from the primary site of H. pylori colonization [11-13]. …”
Section: Discussionmentioning
confidence: 99%
“…A possible association between H. pylori and cardiovascular disorders has been found. The release of cytotoxic substances either of a bacterial origin or produced by the host may represent mediators of these systemic sequelae [11]. Different reports have confirmed the development and association of cytotoxin-associated gene A (cagA) positive H. pylori strains with many clinical problems.…”
Section: Introductionmentioning
confidence: 99%
“…The association between H.pylori infection and elevated blood pressure is controversial [13,14], but it seems that H.pylori eradication could improve blood pressure especially in hypertensive patients [15]. The hypotensive effect of broccoli sprouts is also controversial; supplementation of spontaneously hypertensive stroke-prone rat with broccoli sprouts significantly decreased blood pressure [16], while ingestion of broccoli sprouts had not significant effect on blood pressure and endothelial function measured by flow mediated dilation in hypertensive patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…Individual measures worsened with known or presumed eradication failure (efficacy study): breadth‐of‐base tended to narrow with known eradication failure, visual dependency increased in the ANA positive. Supine mean arterial pressure fell progressively following Helicobacter eradication [53], with a corresponding rise in pulse rate (case history): obesity and fluid retention, associated with elevated serum cortisol [46], may have contributed to initial pressures. Pulse fell with known failure.…”
Section: Discussionmentioning
confidence: 99%